Зниження втрат електроенергії при її передачі та розподіленні - Заболотний, А. П.; Мамбаєва, В. С.; Федоша, Д. В. (НТУ "ХПІ", 2010)
This article discusses the reduction of energy losses in transmission and distribution by optimizing the structure of the electricity grid voltage 10/0,4 kV. The algorithms determine the number and location of units of loads, the choice of power source, the definition of intermediate load units, based on the method of potential surface.
Keywords: електроенергія; енергозбереження; енергозатрати; електропостачання; електромережі